Traversing the Desert: Fascination and Fear in Bertolucci’s The Sheltering Sky (1990)‘Traversing the Desert: Fascination and Fear in Bertolucci’s The Sheltering Sky (1990) (Global Journal of Human-Social Science, 2019)
This article aims at exploring acts of narration and representation of Morocco in Bernardo Bertolucci s The Sheltering Sky 1990 This filmic production offers a critical examination of the representation of the typical Moroccan in Hollywood The Sheltering Sky 1990 offers a rather different narrative mode drifting away from Hollywood traditionalist model of narration writing in bold a new tradition of narration and representation of Morocco Bernardo Bertolucci s The Sheltering Sky 1990 constitutes such a narrative mode that embraces this denigrating and demeaning system of representation Such a system I would say explains how this Hollywood power to represent Morocco could very well nourish the ideological power to dominate and subsequently produce Morocco according to global standards